Pediatric Facial Fractures in South Australia: Epidemiology, Clinical Characteristics, and Outcomes. Issue 7 (9th October 2021) - Diab, Jason; Flapper, Walter J.; Grave, Benjamin; Anderson, Peter J.; Moore, Mark H.
Abstract : Supplemental Digital Content is available in the text Abstract : Introduction: Facial fractures of children are relatively infrequent compared to adults. There are variations in facial fractures depending on the socioeconomic, cultural, and educational factors of the country and time. Our aim is to describe epidemiological trends of facial fractures in the pediatric population, understand differences amongst the age groups, and the impact this has on clinical outcomes and management in South Australia. Methods: A retrospective review was conducted from January 2012 to January 2017 at the Women and Children's Hosptial, Adelaide. All facial fractures of children, aged 16 years and below, that attended or were referred to the unit were included in this study. Results: A total of 265 pediatric patients presented with a facial fracture with a male predominance. Some 49.1% occurred from a sports-related injury with bicycle motocross as the single most common type of sport. The mandible was the common fracture type with 21.9% of the total cohort having an associated injury. There were significant differences between boys and girls for age, age groups, mechanism of injury, and type of sport ( P < 0.05). Boys were 2.3 times more likely to have a sport-related facial fracture than girls. Early adolescence were 5.2 times more likely to have an orbitozygomatic fracture than children of early childhood ( P < 0.05). Age, associated injuries, and sport-related facial fractures were independently associated with increased length of stay ( P < 0.001). Conclusions: There are differences amongst boys and girls and an understanding of these differences can aid the diagnosis and management in a growing child's face.